This business of kidnapping making sense of kidnapping within a business transaction perspective. [article]. - Mateo, Nino Jose .
This paper looked into the personal accounts of Chinese-Filipino kidnap for-ransom victims in Manila. It sought to (a)explore the experience of kidnapping from the point of view of the victims, and (2)discover and make sense of the common features in their experiences. Five respondents were interviewed. The environmental, cognitive and behavioral conditions of the kidnapping ordeal were outlined. The business transaction perspective was then used to structure this information. Similarities were found between kidnapping and a business transaction in that they were both (a)about money, (b) not personal, (c)share similar roles, (d)were governed by similar rules, and (e)temporary. Implications of these similarities were then outlined. This perspective only takes into account the stories included in the research. However, it still offer a fresh way for us to make sense of a phenomenon we know so little about.